Does Hysteresis in Unemployment Occur in OECD Countries? Evidence from Parametric and Non-Parametric Panel Unit Roots Tests - Liew, Venus Khim-Sen; Puah, Chin-Hong; Chia, Ricky Chee-Jiun (Munich Personal RePEc Archive, 2009)
This study tests the hysteresis hypothesis of unemployment in fourteen OECD countries by examining the stationarity of unemployment rates using several panel unit root tests. Empirical results show that the hysteresis hypothesis cannot be rejected for majority of the OECD when the tests are conducted on the basis of individual countries.However, rejection is obtained when cross-country interdependence in unemployment rates is incorporated in the estimation. Therefore, it is crucial to consider the cross-country labor markets interdependence when testing the hysteresis hypothesis as the labor market institutions and the stabilization policy of the labor markets in these OECD countries can play an important role in maintaining the unemployment to sustainable levels.